Orientacja przedsiębiorcza w wyjaśnianiu wczesnej internacjonalizacji przedsiębiorstw - Aleksandra Gaweł (Problemy Zarządzania, 2015)
In Poland, the share of early internationalized companies has been growing, and such companies operate on the international markets almost from their inception. The data of the Global Entrepreneurship Monitor shows that in 2011 the share of enterprises having at least 25% of their customers from abroad was 17% of newly created companies whilst in 2014 it was 24%. It shows that the early internationalization is becoming a fact. In the literature on internationalization, the phenomenon of early internationalization has been observed since the late 1990s. Despite this, there is still no clear answer to the question about the reasons and the process itself.